Studi Projek Trajectories Partikel dalam Medan Magnet Non Homogen di ATLAS dengan Menggunakan Runge-Kutta-Nystrom dan Runge-Kutta-Nystrom Adaptif - Muhammad Ridho Pratama; Fadli Handoyo; Shallu Fidhah Ariyanti; Delila Septiani Dwi Putri; Michael Setiyanto Silambi (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract The problem that arises in the numerical method is the validation of the answers obtained from these calculations. Another phenomenon that can be analyzed using other numerical approaches was also discovered by the European Institute for Nuclear Research, CERN. four giant detectors record the energy-producing Higgs boson particles. One such detector is ATLAS. As for this research, a new adaptive Runge-Kutta-Nystrom method was developed for the STEP algorithm on the ATLAS detector. In solving problems regarding the determination of the second-order ordinary differential equation (2) on the path of particles in the non-homogeneous magnetic field of the ATLAS detector (A Toroidal LHC Apparatus). Two types of modified Runge-Kutta methods were used. This method is the adaptive Runge Kutta Nystrom method which is then compared with the usual Runge Kutta Nystrom method to find the function r(s) which is a 2nd-order differential function. The output table contains data for arc length (s), the radius of curvature (r), the gradient of the function R(dr/ds), and the step size (h).Runge-Kutta Nystrom Table Outputs. Adaptive Runge-Kutta Nystrom Graph Output. Runge-Kutta Nystrom Graph Output. Project Discussion. Based on Algorithm. Based on Time Consumption. Based on Cost-Computation. Based on the Step-Size Difference. Based on the time consumption, the Adaptive Runge-Kutta Nystrom algorithm requires a faster running time than the usual Runge-Kutta Nystrom algorithm. Adaptive Runge-Kutta Nystrom takes 1,095 seconds to run, and Runge Kutta Nystrom takes 2,135 seconds. If it is reviewed based on the computational side which is focused on memory efficiency, the Adaptive Runge-Kutta Nystrom method is better than Runge-Kutta Nystrom. Abstrak Permasalahan yang muncul pada metode numerik adalah validasi jawaban yang diperoleh dari perhitungan tersebut. Fenomena lain yang dapat dianalisis dengan menggunakan pendekatan numerik lainnya juga ditemukan oleh Lembaga Riset Nuklir Eropa, CERN. partikel Higgs boson yang menghasilkan energi direkam oleh empat detektor raksasa. Salah satu detektor tersebut adalah ATLAS. Adapun dalam penelitian ini dikembangkan metode Runge-Kutta-Nystrom adaptif yang baru untuk algoritma STEP pada detektor ATLAS Dalam menyelesaikan persoalan mengenai penentuan persamaan diferensial biasa orde 2 (dua) pada lintasan partikel dalam medan magnet non-homogen detektor ATLAS (A Toroidal LHC Apparatus) digunakan dua jenis metode Runge-Kutta yang dimodisikasi. Metode tersebut yaitu metode Runge Kutta Nystrom adaptif yang kemudian dibandingkan dengan metode Runge Kutta Nystrom biasa untuk mencari fungsi r(s) yang merupakan fungsi diferensial orde 2. Output Tabel yang berisikan data nilai panjang busur (s), jari-jari kelengkungan (r), gradien fungsi R(dr/ds), dan ukuran langkah (h). Output Tabel Runge-Kutta Nystrom. Output Grafik Runge-Kutta Nystrom Adaptif. Output Grafik Runge-Kutta Nystrom. Pembahasan Projek. Berdasarkan Algoritma. Berdasarkan Time Consumption. Berdasarkan Cost-Computation. Berdasarkan Perbedaan Step-Size.Bedasarkan sisi time consumption algoritma Runge-Kutta Nystrom Adaptif membutuhkan waktu running yang lebih cepat dibandingkan algoritma Runge-Kutta Nystrom biasa. Runge-Kutta Nystrom Adaptif membutuhkan waktu running selama 1.095 detik dan Runge Kutta Nystrom membutuhkan waktu selama 2.135 detik. Jika ditinjau berdasarkan sisi komputasi yang difokuskan pada efisiensi memori, maka dapat dikatakan bahwa metode Runge-Kutta Nystrom Adaptif lebih baik dari Runge-Kutta Nystrom.